The Relationship between Transformational Leadership and Building Partnerships on the Performance of Early Childhood Education Principals - Edi Junaedi; Suherman Suherman; Encep Syarifudin (Universitas Negeri Semarang, 2023)
It is important to pay attention to the early childhood learning environment at this time, this has something to do with the leadership style of the school principal. Constraints that are still a problem because the initiative of a leader is still low in carrying out dynamic updates and changes in the Early Childhood Education (ECE) environment, so this can have an impact on performance. The purpose of this study was to determine the relationship between transformational leadership and building partnerships on the performance of ECE principals. The methodology uses quantitative data collection methods based on observation and questionnaires. The research sample consisted of 30 ECE principals selected by random sampling with consideration of school qualifications and experience as school principals. The data analysis technique uses inferential statistics with the SPSS-assisted Independent Samples Test. The findings show that transformational leadership and building partnerships have a significant relationship to the performance of ECE principals. The transformational style can delegate tasks or jobs to teachers, and involve teachers in decision making, pay attention to subordinates, and create a sporty and family work environment. Building partnerships can be started with parents and can then be carried out with the community environment to increase electability and synergy of strong cooperative relationships in achieving optimal educational goals.